MOVEMENT OF A RELATIVISTIC ELECTRON IN CROSSED ELECTRIC AND MAGNETIC FIELDS - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It is shown that the ideas about the electron motion into electric and magnetic crossed fields existing in the modern literature are incorrected. For relativistic velocity case the electron motion can't be imagined by the superposition of the drift with velocity u = E0/B0 and the rotation with frequency  = eB0/m (e, m is charge and mass of relativistic electron). In the relativistic case these motions are not separated, moreover the instantaneous rotation frequency  of relativistic electron is unstable for fixed coordinate system (E0, B0):  depends on m, which varies considerably during rotation.